Targeting heparan sulfate-protein interactions with oligosaccharides and monoclonal antibodies - Li, Miaomiao; Pedersen, Lars C.; Xu, Ding (Frontiers in Molecular Biosciences, 2023)
Heparan sulfate-binding proteins (HSBPs) are structurally diverse extracellular and membrane attached proteins that interact with HS under normal physiological conditions. Interactions with HS offer an additional level of control over the localization and function of HSBPs, which enables them to behave in a more refined manner. Because all cell signaling events start at the cell membrane, and cell-cell communication relies on translocation of soluble factors across the extracellular matrix, HS occupies an apical position in cellular signal transduction by interacting with hundreds of growth factors, cytokines, chemokines, enzymes, enzyme inhibitors, receptors and adhesion molecules. These extracellular and membrane proteins can play important roles in physiological and pathological conditions. For most HS-binding proteins, the interaction with HS represents an essential element in regulating their normal physiological functions. Such dependence on HS suggests that manipulating HS-protein interactions could be explored as a therapeutic strategy to selectively antagonize/activate HS-binding proteins. In this review, we will discuss current understanding of the diverse nature of HS-HSBP interactions, and the latest advancements in targeting the HS-binding site of HSBPs using structurally-defined HS oligosaccharides and monoclonal antibodies.